1993
DOI: 10.1128/jvi.67.6.3470-3480.1993
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus type 1 DNA cleavage and encapsidation require the product of the UL28 gene: isolation and characterization of two UL28 deletion mutants

Abstract: The herpes simplex virus type 1 UL28 gene contains a 785-amino-acid open reading frame that codes for an essential protein. Studies with temperature-sensitive mutants which map to the UL28 gene indicate that the UL28 gene product (ICP18.5) is required for packaging of viral DNA and for expression of viral glycoproteins on the surface of infected cells (C. Addison, F.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
66
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(75 citation statements)
references
References 50 publications
9
66
0
Order By: Relevance
“…Previously described procedures were used for growth and maintenance of African green monkey kidney cells (Vero; ATCC CCL 81 [26]). Vero-derived C1 (49), F3 (19), D6 (11), and 3A6 cells were grown in Dulbecco modified Eagle medium plus 10% fetal bovine serum and 0.5 mg of G418 (Geneticin; GIBCO-BRL) per ml. The KOS strain of HSV-1 was used as the wild-type strain.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously described procedures were used for growth and maintenance of African green monkey kidney cells (Vero; ATCC CCL 81 [26]). Vero-derived C1 (49), F3 (19), D6 (11), and 3A6 cells were grown in Dulbecco modified Eagle medium plus 10% fetal bovine serum and 0.5 mg of G418 (Geneticin; GIBCO-BRL) per ml. The KOS strain of HSV-1 was used as the wild-type strain.…”
Section: Methodsmentioning
confidence: 99%
“…The KOS strain of HSV-1 was used as the wild-type strain. The HSV-1 UL28 deletion mutant GCB (49) was grown on UL28-complementing cell line C1. The UL26 and UL27 null viruses, KUL26⌬Z (19) and K082 (11), were grown on 3A6 and D6 cells, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The translocation of concatenated viral DNA into procapsids and its cleavage at packaging sites is not understood. Recent studies with herpes simplex virus type 1 (HSV-1) mutants defective in UL6, UL15, UL25, UL28, UL32 or UL33 suggest that these genes are essentially involved in viral DNA cleavage and packaging, since cells infected with these mutants produce only B capsids lacking DNA (Al-Kobaisi et al 1991;Baines et al 1997;Weller 1996, 1998;McNab et al 1998;Patel et al 1996;Tengelsen et al 1993;Yu et al 1997). The respective homologues of these genes in HCMV are UL104, UL89, UL77, UL56, UL52 and UL51 (Chee et al 1990).…”
Section: Terminase Inhibitorsmentioning
confidence: 99%
“…Most terminases are hetero-oligomers with each subunit carrying a di¡erent function [11^16]. Mutations in any of the encoding genes lead to an accumulation of empty procapsids/proheads and uncleaved concatemeric DNA in the nucleus [9,17,18]. Our previous data together with the reports from Krosky et al [19] and Underwood et al [20] indicated that the terminase of HCMV consists of the highly conserved proteins pUL56 and pUL89 [212 6].…”
Section: Introductionmentioning
confidence: 99%